الأفلام الوثائقية المفضلة لدى الطلبة المتخصصين في اللغة العربية بالجامعة الإسلامية العالمية بماليزيا = Documentary films preferred by Arabic majoring Students in International Islamic University Malaysia (IIUM) - Tg Abdul Rahman, Tg Ainul Farha; Chik, Abdul Rahman; Sahrir, Muhammad Sabri; Nordin, Fitri Nurul 'Ain (AL-QIYAM Centre for Scientific Research and Studies 21300 Terengganu, Malaysia, 2020)
يُمثل الأفلام الوثائقية مهارة الكتابة بأركانها على مقدمة الموضوع وتقديم أفكارها وخاتمتها، ومن المعلوم أن إعداد النصوص المكتوبة القائمة على البحث العلمي أمرٌ مطلوب من قبل أن يُصنع الفلم الوثائقي؛ لذا للفلم الوثائقي علاقة قوية وقريبة بمهارة الكتابة، وقد تناولت هذه الدراسة ثلاثة أسئلة؛ وهي (1) ما هو مجال الفلم الوثائقي المحبوب من عند الطلبة؟ (2) ما رأيهم الخاص عن نصوص الفلم الطبيعة والبيئة؟ (3) ما رأيهم الخاص عن نصوص والفلم العلوم والتكنولوجيا؟. وتتَّبع هذه الدراسة منهجي كمي وكيفي، إذ تحلل الدراسة عن بيانات من استبانة أسئلة مغلقة للإجابة الأسئلة الثلاث وتحلل الدراسة عن بيانات من استبانة أسئلة مغلقة ومفتوحة للإجابة السوال الثاني والثالث. علمًا أن الاستبانة أُرسلت إلى المصححين للتأكد من مصداقية الاستبانة وثباتها. ثم وُزِّعت الاستبانة على ثمانين طالبًا للكشف عن مجال الفلم الوثائقي المحبوب من عند الطلبة، قبل التعرض إلى تعلم باستخدام الأفلام الوثائقية في الدراسة شبه التجريبية. وتوصَّلت الدراسة إلى أفلام الطبيعة والبيئة أكثر مفضلة عند الطلبة بدلا من أفلام العلوم والتكنولوجيا ****************************************************************************** Documentary films represent the skill of writing with its pillars on the introduction to the topic, presenting its ideas and conclusion, and it is known that preparing written texts based on scientific research is required before the documentary is made. Therefore, the documentary has a strong relationship and close to the skill of writing. Thus, this study addressed three questions; (1) what is the field of documentary film preferred by the students? (2) what do they think about the texts in the nature and the environment documentary films? (3) what do they think about the texts in the science and technology documentary films?. This study applied quantitative and qualitative methodology, as the study analyzes data from closed-ended questions to answer all the research questions, while the study also analyzes data from open-ended questions answer the second and third question. The questionnaire was sent to the experts to verify the accuracy and reliability of the questionnaire. Then the questionnaire was distributed to eighty (80) students to explore the field of documentary film liked by students, before exposure to learning using documentaries in the quasi- experimental study. The study found that nature and environment documentary films are more popular with students rather than science and technology documentary films.